Recent Advances in Radiotracer Imaging Hold Potential for Future Refined Evaluation of Epilepsy in Veterinary Neurology - Bankstahl, Marion; Bankstahl, Jens P. (Frontiers in Veterinary Science, 2017)
Noninvasive nuclear imaging by positron emission tomography and single photon emission computed tomography has significantly contributed to epileptic focus localization in human neurology for several decades now. Offering functional insight into brain alterations, it is also of particular relevance for epilepsy research. Access to these techniques for veterinary medicine is becoming more and more relevant and has already resulted in first studies in canine patients. In view of the substantial proportion of drug-refractory epileptic dogs and cats, image-guided epileptic focus localization will be a prerequisite for selection of patients for surgical focus resection. Moreover, radiotracer imaging holds potential for a better understanding of the pathophysiology of underlying epilepsy syndromes as well as to forecast disease risk after epileptogenic brain insults. Importantly, recent advances in epilepsy research demonstrate the suitability and value of several novel radiotracers for noninvasive assessment of neuroinflammation, blood-brain barrier alterations, and neurotransmitter systems. It is desirable that veterinary epilepsy patients will also benefit from these promising developments in the medium term. This paper reviews the current use of radiotracer imaging in the veterinary epilepsy patient and suggests possible future directions for the technique.